Glyco-Engineering Plants to Produce Helminth Glycoproteins as Prospective Biopharmaceuticals: Recent Advances, Challenges and Future Prospects - van der Kaaij, Alex; van Noort, Kim; Nibbering, Pieter; Wilbers, Ruud H. P.; Schots, Arjen (Frontiers in Plant Science, 2022)
Glycoproteins are the dominant category among approved biopharmaceuticals, indicating their importance as therapeutic proteins. Glycoproteins are decorated with carbohydrate structures (or glycans) in a process called glycosylation. Glycosylation is a post-translational modification that is present in all kingdoms of life, albeit with differences in core modifications, terminal glycan structures, and incorporation of different sugar residues. Glycans play pivotal roles in many biological processes and can impact the efficacy of therapeutic glycoproteins. The majority of biopharmaceuticals are based on human glycoproteins, but non-human glycoproteins, originating from for instance parasitic worms (helminths), form an untapped pool of potential therapeutics for immune-related diseases and vaccine candidates. The production of sufficient quantities of correctly glycosylated putative therapeutic helminth proteins is often challenging and requires extensive engineering of the glycosylation pathway. Therefore, a flexible glycoprotein production system is required that allows straightforward introduction of heterologous glycosylation machinery composed of glycosyltransferases and glycosidases to obtain desired glycan structures. The glycome of plants creates an ideal starting point for N- and O-glyco-engineering of helminth glycans. Plants are also tolerant towards the introduction of heterologous glycosylation enzymes as well as the obtained glycans. Thus, a potent production platform emerges that enables the production of recombinant helminth proteins with unusual glycans. In this review, we discuss recent advances in plant glyco-engineering of potentially therapeutic helminth glycoproteins, challenges and their future prospects.